2016
DOI: 10.1055/s-0036-1571343
|View full text |Cite
|
Sign up to set email alerts
|

Newly-Recognized Roles of Factor XIII in Thrombosis

Abstract: Arterial and venous thrombosis are major contributors to coagulation-associated morbidity and mortality. Greater understanding of mechanisms leading to thrombus formation and stability is expected to lead to improved treatment strategies. Factor XIII (FXIII) is a transglutaminase found in plasma and platelets. During thrombosis, activated FXIII crosslinks fibrin and promotes thrombus stability. Recent studies have provided new information about FXIII activity during coagulation and its effects on clot composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
72
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 109 publications
0
72
0
Order By: Relevance
“…37 Moreover, in vivo studies with factor XIII-deficient mice suggested that this mechanism can modulate thrombus size via cross-linking of fibrin's α-chains. 38,39 Collectively, these findings suggest that platelet-driven, fibrin-mediated clot contraction can play an important role in preventing blood loss, reducing the volume of the clot, and restoring blood flow past otherwise obstructive thrombi. 7,40 Dysfibrinogenemias Dysfibrinogenemia is a collective name for qualitative defects of fibrinogen that affect its functionality, almost invariably the ability to form fibrin clots, as this is usually the mode of discovery, and they can have thrombotic or bleeding consequences or be asymptomatic.…”
Section: Blood Clot Contractionmentioning
confidence: 94%
“…37 Moreover, in vivo studies with factor XIII-deficient mice suggested that this mechanism can modulate thrombus size via cross-linking of fibrin's α-chains. 38,39 Collectively, these findings suggest that platelet-driven, fibrin-mediated clot contraction can play an important role in preventing blood loss, reducing the volume of the clot, and restoring blood flow past otherwise obstructive thrombi. 7,40 Dysfibrinogenemias Dysfibrinogenemia is a collective name for qualitative defects of fibrinogen that affect its functionality, almost invariably the ability to form fibrin clots, as this is usually the mode of discovery, and they can have thrombotic or bleeding consequences or be asymptomatic.…”
Section: Blood Clot Contractionmentioning
confidence: 94%
“…8 Findings on the role of this polymorphism in thrombosis risk have been inconsistent; however, both independent studies and meta-analyses suggest the 34Leu variant offers modest but significant protection against venous thrombosis. [9][10][11][12][13][14] Discovery that the effects of the Val34Leu polymorphism are mediated by gene-environment interactions between FXIII-A genotype and plasma fibrinogen concentration has resolved some of the discord. 15 For example, in the Leiden Thrombophilia Study, although Leu homozygosity showed weak protection against venous thrombosis in men, 16 reanalysis adjusting for fibrinogen concentration strengthened the association for both men and women, especially in individuals older than 45 years.…”
Section: Introductionmentioning
confidence: 99%
“…Fibrin clot structure is dependent upon fibrinogen levels, rates of fibrinopeptide cleavage, and FXIII activity [6, 4346]. Clot architecture could be further controlled by designing FXIII AP sequences that are easier or more difficult to be cleaved by thrombin [27, 41].…”
Section: Introductionmentioning
confidence: 99%